TANTANGAN GURU DALAM PEMBELAJARAN IPA DENGAN PENDEKATAN SAINTIFIK 5M DI SMP - Sonya Rosida; Erman Erman (PENSA: E-JURNAL PENDIDIKAN SAINS, 2021)
This research aimed to analyze and describe the challenges of teachers when learning by using a scientific approach. The type of research used is descriptive qualitative, making descriptions or descriptions related to the challenges of teachers in implementing science learning using a scientific approach. The instrument used in this study was the teacher's challenge instruments in the scientific approach, which contained the stages of the scientific approach and the challenges faced by the teacher. The data collection technique in this study used literature studies and used the subject matter of case studies in research that had been conducted by previous researchers to analyze the challenges or obstacles experienced by teachers when carrying out learning using a scientific approach. The data analysis technique used in this research is content analysis which begins with the process of data collection, data reduction, data presentation, and conclusion drawing. The results obtained in this study are that it is found that there are still many challenges faced by teachers during learning activities. The most dominant challenge for science teachers in scientific learning includes 3 things, namely: the challenge of teachers in planning learning activities, class management, and managing time allocations. Therefore, it is hoped that the school, especially the principal, will provide special training for teachers in preparing lesson plans (RPP) and an explanation of the stages of the scientific approach. That way it can minimize the challenges faced by teachers in schools.